Effect of red blood cells aggregation on scattering coefficient - Szołna-Chodór, A.; Kempczyński, Adam; Grzegorzewski, B. (Photonics Letters of Poland, 2011)
Red blood cells (RBCs) suspended in plasma aggregate. This paper presents a method of determination of scattering coefficient of the RBC suspensions at 632nm wavelength. Blood was obtained from healthy donors. The intensity of coherent component of the scattered light from the suspension located in wedge shaped container was measured during 35 min at sample thickness from 127 to 547µm, at hematocrits 0.01 to 0.04. It is shown that the scattering coefficient linearly decreases with time at the early stages of RBC aggregation. The time dependence of the coefficient becomes nonlinear when the early aggregation is completed. The duration of the early phase of RBC aggregation decreases as hematocrit increases. At very small hematocrits (Ht ≤ 0.01) the scattering coefficient is independent of the thickness of the sample. The effect of the sample thickness on the scattering at higher hematocrits has been demonstrated Full Text: PDF References: A. Pribush, D. Meyerstein, N. Meyerstein, "The mechanism of erythrocyte sedimentation. Part 1: Channeling in sedimenting blood", Colloids and Surfaces B 75, 214 (2010). [CrossRef] J. Mutrynowska, B. Grzegorzewski, "Optical analysis of red blood cell sediment formation ", Biorheology 44, 285 (2007). [DirectLink] A. Pribush, N. Meyerstein, "Methodological Aspects of Erythrocyte Aggregation", Recent Patents on Anti-Cancer Drug Discovery 2, 240 (2007). [CrossRef] E. Ponder, "ON SEDIMENTATION AND ROULEAUX FORMATION—II", Exp. Physiol. 16, 173 (1926) . [DirectLink] D. Kernick, A. W. L. Jay, S. Rowlads, and L. Skibo, "Experiments on Rouleau Formation", Can. J. Physiol. Pharmacol. 51, 690 (1973). [CrossRef] T. Shiga, K. Imaizumi, N. Maeda, K. Kon, "Kinetics of rouleaux formation using TV image analyzer. I. Human erythrocytes", Am. J. Physiol. Heart Circ. Physiol. 245, H259 (1983). [DirectLink] G. Barshtein, D. Wajnblum, S. Yedgar, "Kinetics of Linear Rouleaux Formation Studied by Visual Monitoring of Red Cell Dynamic Organization", Biophys. J. 78, 2470 (2000). [CrossRef] I.Cicha, Y.Suzuki, N.Tateishi, N.Maeda, "Changes of RBC aggregation in oxygenation-deoxygenation: pH dependency and cell morphology", Am. J. Physiol Heart Circ. Physiol. 284, H2335 (2003). [DirectLink] J. M. Steinke, A. P. Shepherd, "Comparison of Mie theory and the light scattering of red blood cells", Appl. Opt. 27, 4027 (1988). [CrossRef] M. Hammer, D. Schweitzer, B. Michel, E. Thamm, A. Kolb, "Single Scattering by Red Blood Cells", Appl. Opt. 37, 7410 (1998) . [CrossRef] O. Ergűl, A. Arslan-Ergűl, L Gűrel, "Computational study of scattering from healthy and diseased red blood cells ", J. Biomed. Opt. 15, 045004 (2010) [CrossRef] A. Roggan, M. Friebel, K. Dörschel, A. Hahn, G. Müller, "Optical Properties of Circulating Human Blood in the Wavelength Range 400–2500 nm ", J. Biomed. Opt. 4, 36 (1999). [CrossRef] A.V. Priezzhev, O.M. Ryaboshapka, N.N. Firsov, I.V. Sirko, "Aggregation and Disaggregation of Erythrocytes in Whole Blood: Study by Backscattering Technique", J. Biomed. Opt. 4, 76 (1999). [CrossRef] M.J. Pearson, H.H. Lipowsky, "Influence of erythrocyte aggregation on leukocyte margination in postcapillary venules of rat mesentery", Am. J. Physiol. Heart Circ. Physiol. 279, H1460 (2000) [DirectLink] S.V. Tsinopoulos, E.J. Sellountos, D. Polyzos, "Light Scattering by Aggregated Red Blood Cells", Appl. Opt. 41, 1408 (2002) [CrossRef] L.D. Shvartsman, I. Fine, "Optical transmission of blood: effect of erythrocyte aggregation", IEEE Trans. Biomed. Eng. 50, 1026 (2003) [CrossRef] C.V.L. Pop, S. Neamtu, "Aggregation of red blood cells in suspension: study by light-scattering technique at small angles ", J. Biomed. Opt. 13, 041308 (2008) [CrossRef] V. Twersky, "Absorption and Multiple Scattering by Biological Suspensions", J. Opt. Soc. Am. 60, 1084 (1970) [CrossRef]